Victims and contemporary tendencies in crime control - Soković Snežana (Temida)
Victimological dimension of new criminality forms is a specific challenge for contemporary criminal law systems; new time brings new forms of criminality, new victims, but also new ways and opportunities for more efficient protection of victims. At the same time with review and improvement of existing standards of victims` protection, contemporary criminality control systems show strong tendency toward compromising the general position of the victim. Victim’s interests are being instrumentalized because of the justification of changes in criminality control in the direction of significant strengthening of criminal law repression. The crime which is emotionalized with the affective media presentation of the victim justifies stricter penal policy and provides the populist support for repressive criminality control strategies and criminal law expansionism. The aim of the paper is the analysis of the mechanisms of victim “use“ in contemporary criminality control and the examination of its consequences, with special review on domestic circumstances through analysis of the Code on special measures for prevention of crimes against sexual freedom towards juveniles (Marija`s Code).